Tooth loss impairs cognitive function in SAMP8 mice by aggravating pyroptosis of microglia via the cGAS/STING pathway - Sun, Xu; Lu, Yunping; Hu, Jiangqi; Meng, Shixiang; Wang, Xiaoyu; Jiang, Qingsong (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s Disease (AD) is a common neurodegenerative disease among the elderly population. It has been posited that the onset and progression of AD are influenced by a combination of various factors. Occlusal support loss due to tooth loss has been reported to be a risk factor triggering cognitive dysfunction. This study aimed to investigate the relationship between tooth loss and cognitive dysfunction and illustrate the role of pyroptosis in advancing Alzheimer’s disease.MethodsMale 5-month-old senescence-accelerated mouse strain P8 (SAMP8) mice were divided into two groups (n = 6): the S (sham-operated) and TL (tooth loss) groups. We assessed spatial memory ability using the Y-maze and Novel Object Recognition (NOR) tests. In addition, we performed pathological and molecular biological assessments of the hippocampus to evaluate pyroptosis-related indicators and changes in cGAS/STING. We further verified the correlation between the two in vitro.ResultsThe pathological section staining revealed an upregulation of GSDMD, a target protein of pyroptosis, and abnormal activation of the cGAS/STING pathway, particularly in microglia, after tooth loss. In vitro, we demonstrated that the BV2 microglia knockdown STING group improved the inflammatory cascade response and down-regulated the pyroptotic features.DiscussionThese data suggest that the occlusal support loss due to tooth loss induces pyroptosis-related protein deposition, which may be intimately associated with the cGAS/STING signaling pathway. This provides new insights into the treatment and prevention of oral health and cognitive behavioural disorders in the elderly population.